2012
DOI: 10.1053/j.gastro.2012.07.097
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Identifies Variants Associated With Progression of Liver Fibrosis From HCV Infection

Abstract: BACKGROUND & AIMS Polymorphisms in IL28B were shown to affect clearance of hepatitis C virus (HCV) infection in genome-wide association (GWA) studies. Only a fraction of patients with chronic HCV infection develop liver fibrosis, a process that might also be affected by genetic factors. We carried out a 2-stage GWA study of liver fibrosis progression related to HCV infection. METHODS We studied well-characterized HCV-infected patients of European descent who had liver biopsies before treatment. We defined va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
134
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(140 citation statements)
references
References 59 publications
(60 reference statements)
2
134
0
4
Order By: Relevance
“…The initial association between MERTK rs4374383 and development of fibrosis in chronic HCV disease was observed in a GWAS; in this study, the association was observed only in a sub-group of HCV patients who received blood transfusions [12]. Later, the MERTK SNP significantly added risk to accelerated fibrosis progression rate in the Swiss Hepatitis C Cohort Study [10].…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The initial association between MERTK rs4374383 and development of fibrosis in chronic HCV disease was observed in a GWAS; in this study, the association was observed only in a sub-group of HCV patients who received blood transfusions [12]. Later, the MERTK SNP significantly added risk to accelerated fibrosis progression rate in the Swiss Hepatitis C Cohort Study [10].…”
Section: Discussionmentioning
confidence: 60%
“…A large GWAS has shown that a locus in the RNF7 gene is associated with the development of liver fibrosis in chronic hepatitis C [12]. The study reported that in the combined cohort of 2,342 HCV-infected patients rs16851720 was associated with fibrosis progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…При этом на течение и исходы хронических вирусных гепатитов ока-зывает влияние, вероятно, наличие полимор-физма не в одном, а в нескольких генах и опре-деленная их комбинация [22,29].…”
unclassified